2023
DOI: 10.3390/biomimetics8010018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bionic Tube with High Bending-Stiffness Properties Based on Human Tibiofibular Shapes

Abstract: The human tibiofibular complex has undergone a long evolutionary process, giving its structure a high bearing-capacity. The distinct tibiofibular shape can be used in engineering to acquire excellent mechanical properties. In this paper, four types of bionic tubes were designed by extracting the dimensions of different cross-sections of human tibia–fibula. They had the same outer profiles, but different inner shapes. The concept of specific stiffness was introduced to evaluate the mechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Researchers have shown that biomimetic structures offer superior strength-to-weight ratios compared to traditional materials [18,19], making them crucial in modern industry to meet the demand for efficient and cost-effective solutions [20,21]. Drawing inspiration from nature, researchers have designed structures for enhanced energy absorption through improved deformation coordination and stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that biomimetic structures offer superior strength-to-weight ratios compared to traditional materials [18,19], making them crucial in modern industry to meet the demand for efficient and cost-effective solutions [20,21]. Drawing inspiration from nature, researchers have designed structures for enhanced energy absorption through improved deformation coordination and stress distribution.…”
Section: Introductionmentioning
confidence: 99%